Shortcomings mentioned by the Torah about the prophet Lot in the prophecies and the respond of Quran (Journal of the College of Education for Women, 2019)
Praise be to Allah , and peace and blessings of God sent mercy to the worlds MuhammadAmin and his family and his friends and followers to the Day of Judgement .Savants Jews worked to distort the Torah calamity on the Prophet Moses ( peace be uponhim ) to achieve their goals and objectives , which are decorating sin to their followers , andspreading corruption on earth, through the charge prophets Bmvassad , morality, as theexample and the example that emulate the human in the book of the Lord of the worlds andtheir Prophet Lot, described the weak, and cheese, and lack of modesty, and disobedience ,drinking alcohol , and his failure to raise his two daughters , Jews are corrupt in the ground .Koran , which is the seal and dominated , and completely dominate that reveals many aspectsof distortion and change that entered on the books , the Quran was and still trusted source ofinformation is correct , which is not done wrong , however hands of his successor , revealingaspects of distortion and switches that have occurred on those books, including TorahMazkrth for Prophet Lot ( peace and blessings be upon him ) of disadvantages , has absolvedGod from every gain of Torah to him, has necessitated the wisdom of the Almighty to beprophets fuller human beings created and created , and believe them in word , and the mostproportions , and the very best note , and guided them nimble , Mbrin defects, because theprophets if they are not also small their business in the eyes of the people , and when heanswered them one , so all the prophets lived all their lives infallible white page from fallinginto even become their sins after death lamps illuminate humanity through Rashad and NoorHidayat .May Allah bless our Prophet Muhammad , his family , and his companions , much peace andrecognition .